Advancing the Modelling Environment for the Safety Assessment of the Swedish LILW Repository at Forsmark. Issue 1744 (2015) - von Schenck, Henrik; Kautsky, Ulrik; Gylling, Björn; Abarca, Elena; Molinero, Jorge
ABSTRACT: An extension of the Swedish final repository for short-lived radioactive waste (SFR) is planned and a safety assessment has been performed as part of the licensing process. Within this work, steps have been taken to advance the modelling environment to better integrate its individual parts. It is desirable that an integrating modelling environment provides the framework to set up and solve a consistent hierarchy of models on different scales. As a consequence, the consistent connection between software tools and models needs to be considered, related to the full assessment domain. It should also be possible to include the associated geometry and material descriptions, minimizing simplifications of conceptual understanding. The usefulness of the analysis software Comsol Multiphysics as component of an integrating modelling environment has been tested. Here, we present two examples of hierarchical models. Consistent properties and boundary conditions have been extracted form regional hydrogeology and surface hydrology models when setting up repository scale models. CAD models of the repository have been imported into the analysis software, representing tunnel systems and storage vaults with engineered structures and barriers. Data from geographic information systems such as digital elevation models and geological formations have been also directly implemented into model geometries. The repository scale hydrology models have provided a basis for further developments focussed on the modelling of coupled processes. An interface between Comsol Multiphysics and the geochemical simulator Phreeqc has been developed to support reactive solute transport studies. An important test case concerns radionuclide transport in a 3D, near-surface model of a catchment area. The dynamic surface hydrology has been simulated with MIKE SHE and connected to Comsol Multiphysics and Phreeqc for detailed hydro-geo-chemical modelling of radionuclide migration through soils and sediments.